Development of a Practicum Module Oriented to Chemoentrpreneurship with Qur'an and Hadist Insight on Colloidal System Material - Roni, Roni; Mawarnis, Elvy Rahmi; Herman, Mimi (Hydrogen: Jurnal Kependidikan Kimia, 2023)
This study aims to develop a practicum module oriented to ChemoentrepreneurshipÂ  with Qur'an and Hadith insight on colloidal system material for Class XI SMA/MA that is valid and practical. This study used the Research and Development (R&D) research method with the 4-D development model (define, design, develop, and disseminate). Data for the defining stage was collected using an instrument in the form of an interview sheet. The interview sheet was filled in by the chemistry teacher. Data for the development stage was collected with instruments in the form of validity sheets and practicality questionnaires. Validation were completed by chemistry lecturers and chemistry teacher. Practicality questionnaire sheets were completed by the students as respondent. Data from validity and practicality instruments were analyzed using descriptive quantitative methods, with the percentage formula.The results showed that the practicum module oriented to Chemoentrepreneurship with Qur'an and Hadith Insight on the material of the colloidal system of class XI SMA / MA was categorized as valid with a percentage of 87.79%. In addition, the practicum module oriented Chemoentrepreneurship with Qur'an and Hadith insight on colloidal system material has met the practical criteria with the results of the student response questionnaire 86.80%. Thus, it is known that the practicum module oriented Chemoentrepreneurship Insightful Qur'an and Hadith on colloidal system material class XI SMA/MA has been valid and practical. The results of this study indicate that the practicum module developed can be used as one of the learning resources for students.